2017
DOI: 10.5430/ijhe.v6n2p121
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Overcoming Barriers: Learning Experiences of Undergraduate Sudanese Students at an Australian University

Abstract: An increase in migration of Sudanese and South Sudanese people to Australia due to civil unrest in their home country has increased the numbers of Sudanese students at university. Migrant experiences, particularly those of English as a second language, can impact negatively on education and learning. Inconsistencies between student scores on assessments and oral abilities in class prompted an exploratory project to identify barriers to success and create appropriate resources for students. The project utilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Most findings regarding the motivational structure of NTSs are in accord with measurements by other tools (Francois, 2014;Bye, Pushkar, & Conway, 2007) and confirm higher levels of intrinsic motivation in NTSs (Shillingford & Karlin, 2013;Fazey & Fazey, 2001). A study of Sudanese NTSs at an Australian university where predominantly extrinsic motivation was measured represents an exception to the rule (Gately, Ellis, Britton, & Fleming, 2017). This result can be explained by the subsequent qualitative inquiry revealing perceptions of studies as means to support a family in this ethnically specific group of NTSs.…”
Section: The Academic Motivation Scale and Research On Non-traditionasupporting
confidence: 62%
“…Most findings regarding the motivational structure of NTSs are in accord with measurements by other tools (Francois, 2014;Bye, Pushkar, & Conway, 2007) and confirm higher levels of intrinsic motivation in NTSs (Shillingford & Karlin, 2013;Fazey & Fazey, 2001). A study of Sudanese NTSs at an Australian university where predominantly extrinsic motivation was measured represents an exception to the rule (Gately, Ellis, Britton, & Fleming, 2017). This result can be explained by the subsequent qualitative inquiry revealing perceptions of studies as means to support a family in this ethnically specific group of NTSs.…”
Section: The Academic Motivation Scale and Research On Non-traditionasupporting
confidence: 62%
“…Harris and Marlowe (2011) researched the experiences of a group of young Africans from refugee backgrounds who were studying at a South Australian university, and reported that the students had little understanding of the expectations of Australian educational institutions and accessing study materials and studying in another language (see also Adusei-Asante and Doh, 2016;Harry, 2008;Harris and Marlowe, 2011;Wickramaarachchi and Burns, 2016). Gately, Ellis, Britton and Fleming (2017) used a multi-method approach to investigate the experiences of twenty-two Sudanese students at Western Australia's Edith Cowan University. Based on data obtained from the university, Gately et al, 2017, p.121) reported that:…”
Section: Education Sectormentioning
confidence: 99%
“…Personal attributes that disadvantaged students have to succeed relate to perseverance, resilience, determination and motivation (Luzeckyj et al, 2017). Motivation, is a large factor in overcoming barriers and studies indicate that despite barriers, intrinsically motivated students are more likely to succeed (Gately et al, 2017; Próspero & Vohra‐Gupta, 2007; Trevino & DeFreitas, 2014). PFiF students frequently perform well academically in high school, indicating they possess both the learning skills and the motivation to succeed at university (Spengen, 2013).…”
Section: Introductionmentioning
confidence: 99%